Pengaruh Visi Misi dan Etos Kerja Guru Terhadap Mutu Pendidikan SMP Negeri di Tanjung Lubuk OKI - Syamsiah Syamsiah; Nur Ahyani; Muhammad Fahmi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to determine and analyze: (1) the effect of the implementation of the school vision and mission on educational quality; (2) the effect of teachers‟ work ethic on educational quality; and (3) the simultaneous effect of the implementation of the school vision and mission and teachers‟ work ethic on educational quality in public junior high schools in Tanjung Lubuk District, Ogan Komering Ilir Regency. This research employed a quantitative approach with a descriptive method. The study was conducted in public junior high schools in Tanjung Lubuk District, Ogan Komering Ilir Regency, from July to October 2025. The population of this study consisted of principals and teachers, with samples selected using proportional random sampling. Data were collected through questionnaires, observation, and documentation. Data analysis techniques included simple regression analysis, multiple regression analysis, t-test, and F- test. The results showed that the implementation of the school vision and mission had a significant effect on educational quality, with a t-value of 7.887 greater than the t-table value of 1.662 and a coefficient of determination of 0.526 or 52.6%. Teachers‟ work ethic also had a significant effect on educational quality, with a t- value of 2.522 greater than or equal to the t-table value of 1.662 and an R Square value of 0.231 or 23.1%. Simultaneously, the implementation of the school vision and mission and teachers‟ work ethic had a significant effect on educational quality, with an F-value of 52.842 greater than the F-table value of 3.10 and a contribution of 56%, while the remaining 44% was influenced by other factors not examined in this study.